أحكام التأمينات النقدية الموثقة للتعامل وعلاقتها بالرهن : (Financial Transactions of Cash Insurance Reserved in Forms and Its Relationship with Mortgage) - (Mahmoud Abdel Karim Irshaid), محمود عبد الكريم إرشيد (At-Tajdid - Intellectual Refereed Journal, 2021)
Abstract This study tackles the collateral cash and all its forms in financial transactions, outstanding accounts and all retained money to register the business transactions, such as deposit money and insurance services of all kinds in terms of provision of such funds and the differences or similarities between the types, if any. The study tackles the adaptation of this money to Fiqh (jurisprudence), whether it should be developed and to whom the profit goes if the money were traded? Given the magnitude of the retained money and its effects on sales and service delivery we must discuss its Zakah if it reaches legitimate quorum, and who shall pay this share for the Zakah whether in trading, as well as money reserves held in work related contracts. The objective of this research is to study the provisions of these reserved accounts in terms of the conditions of Fiqh; whether or not it is an assertion tool and to state other similar or different aspects between the multi-labeled transactions. The study found that there are differences between these kinds of funds and that the general acceptance of the transaction affects the nature of the custom thereby reducing its due rights. The research will show the eligibility of investing these funds in Islamic banks for the benefits of both parties in case of an obligation to pay dues after its delivery to the bank for the purpose of investment. This is conditional to several controls and legal requirements for this investment to be made feasible by the bank. Keywords: cash insurance, collateral, deposit money, amount of retained money for business transaction